Detection of novel Plasmodium falciparum coronin gene mutations in a recrudescent ACT-treated patient in South-Western Nigeria - Ajibaye, Olusola; Olukosi, Yetunde Adeola; Oriero, Eniyou C.; Oboh, Mary Aigbiremo; Iwalokun, Bamidele; Nwankwo, Ikechukwu Chidiebere; Nnam, Chinaza Favour; Adaramoye, Olawunmi Victoria; Chukwemeka, Somadina; Okanazu, Judith; Gabriel, Eniafe; Balogun, Emmanuel Oluwadare; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Routine surveillance for antimalarial drug resistance is critical to sustaining the efficacy of artemisinin-based Combination Therapies (ACTs). Plasmodium falciparum kelch-13 (Pfkelch-13) and non-Pfkelch-13 artemisinin (ART) resistance-associated mutations are uncommon in Africa. We investigated polymorphisms in Plasmodium falciparum actin-binding protein (Pfcoronin) associated with in vivo reduced sensitivity to ART in Nigeria. Methods Fifty-two P. falciparum malaria subjects who met the inclusion criteria were followed up in a 28-day therapeutic efficacy study of artemether-lumefantrine in Lagos, Nigeria. Parasite detection was done by microscopy and molecular diagnostic approaches involving PCR amplification of genes for Pf18S rRNA, varATS, telomere-associated repetitive elements-2 (TARE-2). Pfcoronin and Pfkelch-13 genes were sequenced bi-directionally while clonality of infections was determined using 12 neutral P. falciparum microsatellite loci and msp2 analyses. Antimalarial drugs (sulfadoxine-pyrimethamine, amodiaquine, chloroquine and some quinolones) resistance variants (DHFR_51, DHFR_59, DHFR_108, DHFR_164, MDR1_86, MDR1_184, DHPS_581 and DHPS_613) were genotyped by high-resolution melting (HRM) analysis. Results A total of 7 (26.92%) cases were identified either as early treatment failure, late parasitological failure or late clinical failure. Of the four post-treatment infections identified as recrudescence by msp2 genotypes, only one was classified as recrudescence by multilocus microsatellites genotyping. Microsatellite analysis revealed no significant difference in the mean allelic diversity, He, (P = 0.19, Mann-Whitney test). Allele sizes and frequency per locus implicated one isolate. Genetic analysis of this isolate identified two new Pfcoronin SNVs (I68G and L173F) in addition to the P76S earlier reported. Linkage-Disequilibrium as a standardized association index, IAS, between multiple P. falciparum loci revealed significant LD (IAS = 0.2865, P=0.02, Monte-Carlo simulation) around the neutral microsatellite loci. The pfdhfr/pfdhps/pfmdr1 drug resistance-associated haplotypes combinations, (108T/N/51I/164L/59R/581G/86Y/184F), were observed in two samples. Conclusion Pfcoronin mutations identified in this study, with potential to impact parasite clearance, may guide investigations on emerging ART tolerance in Nigeria, and West African endemic countries.